Communication Tactics of Conflict Genesis in the Network Media Space of Frontier Regions - Sergey N. Bredikhin; Evgenii A. Avdeev; Boris A. Shishkin (Галактика медиа: журнал медиа исследований)
The growth of social and political tension in the world, the resonance of global and regional crises and contradictions are preparing new challenges for local linguistic and cultural communities, which are reflected and intensified in network communication. The formation and circulation of conflict-producing content and the use of verbal aggression on social networks can become triggers for ethno-confessional conflicts and provoke aggression and violence. The purpose of the article is to analyze conflict-producing content in the VKontakte communities and Telegram channels of Stavropol, Dagestan and North Ossetia, establish its thematic focus, identify the communication tactics used and speech moves to provoke ethno-confessional conflict. In social networks of the Stavropol region, speech moves are more often used focusing attention on socio-economic difficulties and aimed at creating a hostile attitude towards migrants. In the online discourse of Dagestan, religious themes prevail over ethnic ones, while this factor in determining stratagem-tactical variation helps reduce interethnic and interfaith hostility. The thematic and situational connection of conflict genesis to the initial post suggests that provoking conflict acquires not only an ethnic, but also a confessional character, due to a sense of religious solidarity, and defensive rhetoric in relation to the Islamic way of life and traditions. The analysis of the conflict-producing content of online communities in North Ossetia indicates that there are currently no serious ethnic and religious contradictions, while socio-economic issues are coming to the fore. Significant ethno-confessional and ethnocultural differences, complexities and problems of socio-economic development can turn social networks into an effective tool for the use of manipulative technologies in the course of modern hybrid information warfare. Further research into network discourse will contribute to identifying the conflict-generating potential of verbal aggression and will help to form of effective means of countering the growing threats of destabilization of ethno-confessional relations in the North Caucasus.